Feasibility of deploying community health workers to assist with health-related social needs and hypertension in community care clinics - Brian Robusto; Iris Cheng; Rohan Mahabaleshwarkar; Jessica McCutcheon; Nancy Denizard-Thompson; Sara R. Kinny; Selina Quinones; Henry Bundy; Yhenneko J. Taylor; Deepak Palakshappa (Journal of Clinical and Translational Science)
We conducted a pilot study of implementing community health workers (CHWs) to assist patients with hypertension and social needs. As part of clinical care, patients identified as having an unmet need were referred to a CHW. We evaluated changes in blood pressure and needs among 35 patients and conducted interviews to understand participants’ experiences. Participants had a mean age of 54.1 years and 29 were Black. Twenty-six completed follow-up. Blood pressure and social needs improved from baseline to 6 months. Participants reported being accepting of CHWs, but also challenges with establishing a relationship with a CHW and being unclear about their role.